Transit-oriented development in the metropolitan governance: a comparison between the Colombian case and the South Korean experience - Natalia da Silveira-Arruda; Claudia Marcela Aldana-Ramírez; Carlos Alberto Palacio-Tobón; Diana Patricia Moreno-Palacio (Revista Facultad de Ingeniería Universidad de Antioquia, 2017)
This research studies the process and the political decisions that were carried out in the creation of Seoul Metropolitan Area (SMA) in order to respond to a territorial reorganization associated to a public transport supply that resulted in a model of transit-oriented development (TOD). Contemporaneously, the paper studies the normative framework that governs the metropolitan areas in Colombia and its metropolitan public transport, as well as, it studies the structuring of the metropolitan collective public transport system of the Aburrá Valley Metropolitan Area (AVMA). The aim of the research is to understand the process of territorial and transport policy decisions that were held in the SMA, which makes it an example and case of study to contextualize a reorganization of the collective public transportation system in the Colombian case, specifically in the AVMA. The objectives of the research are identifying the regulatory principles of territorial and transport planning, strategies, and instruments used for setting the policy decisions that have a binding character on the operating entities of the collective public transport system. In order to put the characteristics of the AVMA collective public transport bus system in evidence, a comparison between SMA and AVMA was developed. The implications emerged from this comparison are used to generate guidelines through three themes: a) governance; b) financial system and c) operational aspects. The guidelines hope point the reorganization of the public transportation bus system and a future transition to a model of Transport -and People - Oriented Development in the Colombian metropolitan level context.